Stability Analysis of a Slope considering Two Reinforcement Processes - Wei Chen; Dongbai Li; Ting Ma; Helin Fu; Yanpeng Du (Geofluids)
The strength reduction method embedded in a distinct element code was used to analyse the stability of a slope in a coal mining area that had been reinforced twice, primarily with pile and retaining wall, followed by porous steel-tube bored grouting. For the primary reinforcement, the factor of safety was calculated, slip surface and failure mechanism were determined, and the damage phenomenon of primary reinforcement was analysed in detail. Failure time of slope without further strengthening was predicted by applying a new quantitative method based on monitoring displacement data. The slope instability at the primary reinforced stage was verified by these analyses. For the second reinforcement, the effect was evaluated by combining the new factor of safety and the final monitoring data, which validates the slope stability. Especially, variations of displacement and factor of safety due to water influence are analysed. Through this procedure, a systemic method for the slope safety evaluation and assurance is presented for engineering practice reference.